X-Ray Diffraction Studies on Selected Bacterial Cell Walls - Carito, Sebastian L. (1967)
The cell walls of selected bacteria were studied by X-ray diffraction analysis to determine and characterize crystalline components. The walls were isolated by mechanical disruption and purified by enzymatic and washing procedures. The X-ray diffraction lines which appeared from the gram-positive cell walls were shown to be due to the constituent “mucopeptide” fraction. No diffraction lines could be obtained from the gram-negative bacterium studied. The results show that crystallinity is associated with mucopeptide.